2022
DOI: 10.1002/casp.2653
|View full text |Cite
|
Sign up to set email alerts
|

The role of ethnic enclaves in Arab American Muslim adolescent perceived discrimination

Abstract: This study aimed to investigate the role of ethnic enclaves in perceived discrimination among Arab American adolescents. Little research has investigated what specific risk and protective factors play a role in perceived discrimination within ethnic enclaves; and which of these factors may be the most salient to Arab American adolescents. The study used a phenomenological approach, using semi‐structured interviews, journals, and parent interviews to collect and triangulate the data. Member checking and peer de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 65 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…Previous literature has demonstrated that connection to one’s community has been associated with neighborhood safety, trust, volunteerism, economic prosperity, community resilience, and access to services and supports [ 39 , 91 ]. Being strongly community-connected and integrated within one’s own ethnic enclave may serve as a protective factor for immigrants against outsider discrimination and thereby facilitate positive physical and mental health, well-being, engagement in health-promoting behaviors, and decreased mortality [ 122 , 123 , 124 , 125 , 126 ]. Social disconnection has been associated with isolation and loneliness due to limited or inadequate meaningful connections with others [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has demonstrated that connection to one’s community has been associated with neighborhood safety, trust, volunteerism, economic prosperity, community resilience, and access to services and supports [ 39 , 91 ]. Being strongly community-connected and integrated within one’s own ethnic enclave may serve as a protective factor for immigrants against outsider discrimination and thereby facilitate positive physical and mental health, well-being, engagement in health-promoting behaviors, and decreased mortality [ 122 , 123 , 124 , 125 , 126 ]. Social disconnection has been associated with isolation and loneliness due to limited or inadequate meaningful connections with others [ 113 ].…”
Section: Discussionmentioning
confidence: 99%
“…Institutional resources may include access to public parks, health services, and afterschool programs (Molnar et al, 2008; Pate et al, 2008). Cultural resources and processes include having access to the co‐ethnic community, services in appropriate languages, and institutions that celebrate heritage cultural holidays or support exchange with countries of origin (Balaghi, 2023; Yoshikawa, 2011). Positive social processes include social cohesion, informal social control, and street safety (Sampson et al, 1997).…”
Section: Inhibiting and Promoting Characteristics Of Neighborhood Env...mentioning
confidence: 99%